The Use of Wearable Technology for Cardiovascular Health Monitoring: An Evidence-Based Perspective (Oshada, 2025)
Cardiovascular disease remains the leading cause of global morbidity and mortality, highlighting the need for more preventive and continuous health monitoring approaches. The rapid development of wearable technology offers real-time and continuous cardiovascular monitoring; however, the strength of scientific evidence supporting its effectiveness remains inconsistent. This study aims to systematically analyze the use of wearable technology in cardiovascular health monitoring from an evidence-based perspective. A Systematic Literature Review with an evidence-based approach was conducted using peer-reviewed journal articles retrieved from Scopus, PubMed, Web of Science, and ScienceDirect. Following a PRISMA-based selection process, 38 articles met the inclusion criteria and were qualitatively synthesized. The findings indicate that wearable technology demonstrates relatively strong effectiveness in heart rate monitoring and early screening of cardiac arrhythmias, while evidence for more complex clinical parameters such as blood pressure and heart failure monitoring remains limited and inconsistent. The existing literature is predominantly characterized by non-randomized studies and short-term clinical validation. This study concludes that wearable technology should be positioned as an adjunct to evidence-based clinical practice rather than a substitute for conventional medical examinations and underscores the need for stronger methodological designs and supportive regulatory frameworks in digital health.